Adolescents' Experiences and Perspectives on Physical Activity and Friend Influences Over Time. Issue 3 (3rd July 2021) - Martins, João; Rodrigues, António; Marques, Adilson; Cale, Lorraine; Carreiro da Costa, Francisco
ABSTRACT: Purpose : Understanding friend influences on adolescents' PA, and how these change over time, is fundamental to developing interventions for promoting active lifestyles yet the latter in particular remains unexplored. This study explored the experiences and perspectives of physically active and inactive adolescents regarding the influence of their friends on their PA throughout childhood and adolescence. Methods : Following the completion of a questionnaire, 16 adolescents, 8 boys (4 physically inactive, 4 active) and 8 girls (4 inactive, 4 active), aged 17 ± 1.0 years, were selected from two schools. A qualitative design was adopted whereby each adolescent was interviewed individually. Using the constant comparative method, the interviews were inductively and thematically analyzed. Results : Four main themes were identified: I) PA journeys ; II) Friends provide PA benefits) ; III) Friends matter in PA, but change ; IV) Against all odds—rising above others . Compared to the inactive, active adolescents perceived that their friends were fundamental to them becoming and remaining active, specifically in terms of: offering support to internalize an active sense of belonging in different contexts when family support diminished; providing opportunities to be active at key transition points; and helping them to overcome peer victimization. Conclusion : This study confirms the important role of friends in adolescents' PA, and provides new evidence concerning the changing patterns and influence of friends from childhood to late adolescence. Recommendations are made relating to the role of friends in youth PA with a view to improving the effectiveness of approaches to promoting active lifestyles.